Sinergi Gereja dan Orang Tua dalam Mempersiapkan Anak Mengikuti Perjamuan Kudus: Tantangan dan Solusinya di Gereja Kristen Jawa - Juntak, Justin Niaga Siman; Tarumasely, Yowelna; Sahertian, Christiana Demaja Wilhelmina; ., Kristriyanto; Wahyudi, Sabda (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to understand how the practice of Children's Holy Communion at Gereja Kristen Jawa Dagen-Palur and GKJ Danukusuman is implemented as part of Christian education for children. The subjects of this study include parents of children who have participated in the Children's Holy Communion and church pastors. A qualitative approach with a case study method was employed to gain an in-depth understanding through interviews, observation, and document analysis. The findings indicate that while the Children's Holy Communion can serve as a significant moment in the growth of a child's faith, the follow-up discipleship efforts remain suboptimal. The churches face challenges in designing structured follow-up programs, and parental involvement in accompanying their children's faith journey is still limited. As a result, the continuity of Christian faith education for children is not well maintained. Therefore, this study recommends that churches develop post-communion discipleship programs that actively involve families.